1991
DOI: 10.1002/mawe.19910220304
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of the criteria for multiaxial Random Fatigue

Abstract: In the paper the spectral analysis of several fatigue criteria under simple and complex states of stress has been done and limitations appearing while formulating new criteria for multiaxial random loadings have been shown. The presented analysis includes determination, with digital simulation, of probability density function and power spectral density function of the equivalent stress according to three special linear criteria of multiaxial random fatigue and six nonlinear criteria. Calculations were carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…In an early work at Opole University by the group of Ewald Macha, an equivalent uniaxial stress is determined from the general multiaxial stress state with irregular (possibly random) time courses by using classic static strength criteria, like that of the maximum principal stress (Galileo–Rankine), maximum shear stress (Tresca), deviatoric strain energy (Huber–Hencky–Mises), total strain energy (Beltrami). The main drawbacks in using these static criteria are highlighted in the paper of Macha and coworkers . In particular, it is shown that, in the presence of non‐proportional loading, these criteria do not account for rotating principal stress directions.…”
Section: Time Domain (Numerical Deterministic) Approaches For Multiamentioning
confidence: 99%
“…In an early work at Opole University by the group of Ewald Macha, an equivalent uniaxial stress is determined from the general multiaxial stress state with irregular (possibly random) time courses by using classic static strength criteria, like that of the maximum principal stress (Galileo–Rankine), maximum shear stress (Tresca), deviatoric strain energy (Huber–Hencky–Mises), total strain energy (Beltrami). The main drawbacks in using these static criteria are highlighted in the paper of Macha and coworkers . In particular, it is shown that, in the presence of non‐proportional loading, these criteria do not account for rotating principal stress directions.…”
Section: Time Domain (Numerical Deterministic) Approaches For Multiamentioning
confidence: 99%
“…In 1991, Macha, Grzelak and Łagoda [14] attempted to apply spectral method to determine fatigue life. Studies on these issues were continued further in cooperation with Niesłony [15].…”
Section: Mathematical Models and Their Experimental Verificationmentioning
confidence: 99%
“…In [9] it has been shown that the criteria for variable amplitude loadings must be linear in order to avoid an unfavorable wide frequency band and the mean value occurrence. In [19] Macha formulated the generalized fatigue criterion in stress approach.…”
Section: Introductionmentioning
confidence: 99%